If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -4(x + -6) = 12 Reorder the terms: -5x + -4(-6 + x) = 12 -5x + (-6 * -4 + x * -4) = 12 -5x + (24 + -4x) = 12 Reorder the terms: 24 + -5x + -4x = 12 Combine like terms: -5x + -4x = -9x 24 + -9x = 12 Solving 24 + -9x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -9x = 12 + -24 Combine like terms: 24 + -24 = 0 0 + -9x = 12 + -24 -9x = 12 + -24 Combine like terms: 12 + -24 = -12 -9x = -12 Divide each side by '-9'. x = 1.333333333 Simplifying x = 1.333333333
| (x)+3=5 | | (2x^2-4x)(6x^2-5x)=equation | | k/9=67 | | -2m=5m+68 | | 10p*79l=36666 | | 6m+7m=52 | | -5/9+x=3/4 | | 34j=56 | | x/12=-6 | | (x^2+2x+1)(x^2+4x+4)=equation | | (x^3+4x^2+5x+2)(x+2)=equation | | 3*(1-x)-5*(x+2)=1-4x | | 4(x-3)+3ax=5x-9 | | 6t+5=7t-3 | | 7.3=a/5+1/2 | | -6(3b+4)+(19b-9)=0 | | 10=a/-4 | | 2*(2+x)+3*(4x-1)=10x-7 | | 2a^2-3=0 | | 3x^2-17x=-2x^2-5x-4 | | 3.6q-5.7-2.8q=-0.2q-1.5 | | 3x^2+10x-9=19-7x | | 10x=14(x+1) | | 200/0.85 | | -3p+2=23 | | 7x^2+14x-20=16-5x | | -11=5+v/3 | | (x-6/5x)+1=(x+2/x) | | (6x)(8x)=48 | | 3/4y+6-82=6/8x+24 | | 3y+3=-4y+1 | | 17+34=38 |